The importance of the quality of jumps in figure skating - Blenke, J.; Knoll, Ka. (World Congress of Performance Analysis of Sport VIII, 2008)
For a top final competition rank in figure skating a high quality of the elements is needed. The high level of performance of the top ten is compared, so the influence of high quality is crucial. Only with both, a sufficiently high degree of difficulty as well as a very high quality of execution with only small deductions, a medal position can be reached. Reasoned in the greater deductions for falling, athletes most likely will not risk elements too difficult to perform. Only stable jumps will be performed to avoid faults and falls. Thus, security is crucial to get high quality of execution. If the quality is better, the programme components are higher and so a successful placement is possible. It is important to make a successful training, because jumps can only be shown effectually in competition, if they can be performed stable in training. Since 2008 the regulation of quadruple jumps has changed. They are being scored with points by landing successfully. Consequently, the athletes will show most likely more quadruple jumps in the next season.